PALYNOASSEMBLAGES FROM DEPOSITS OF THE CRATER LAKES OF THE TUNGUSKA PALEOVOLCANIC AREA - Naumov V.A.; Luzina I.V. (My University, 1997)
The studied palynoassemblages were collected from the maar lacustrine sediments deposited in the upper parts of the completed pipe structures located in the south and southeast of the Tunguska paleovolcanic area. The assemblages are compared with those from the Putorana and Dvurogii phytostratigraphic horizons. As inferred, in the south and southeast of the Tunguska syneclise, the large-scale volcanism and ore-forming processes terminated in the pre-Neryunda time. Since the acritarchs, which are best adapted to water with normal (sea) salinity, are persistent components of the palynoassemblages, they can serve as indicators of pipe structures in paleovolcanic reconstructions and prospecting for iron ore.